Kajian Teologis Keselamatan Bayi Dalam Perspektif Jhon Calvin Dan Implikasinya Bagi Warga Gereja Toraja (International Forum of Researchers and Lecturers, 2023)
This paper aims to describe the safety of babies in the Perspective of John Calvin and the Implications for Toraja Church members. The diversity of views on the direction of infant safety in the understanding of Church members has encouraged the author to study infant safety in the view of Jhon Calvin because the Toraja Church is a Calvinist sect. There are those who think that a baby who is born and then dies is still safe even though he has not acknowledged God as his savior. It is like a white paper without blemishes. Another understanding says that all babies who are born and then die He is a sinful human because from the womb he has been conceived and begotten in sin, and regarding salvation it is in God's Sovereignty. The research method used in this paper is literature review. The author seeks and collects the writings of John Calvin, especially on death and salvation, then compiles them. According to John Calvin, salvation is a belief based on faith in Christ. In John Calvin's view, the safety of babies is in God's Sovereignty